2014
DOI: 10.1186/cc13864
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the mechanisms involved in B-type natriuretic peptide elevation and its prognostic value in septic patients

Abstract: IntroductionElevated plasma B-type natriuretic peptide (BNP) levels in patients with critical sepsis (severe sepsis and septic shock) may indicate septic cardiomyopathy. However, multiple heterogeneous conditions may also be involved in increased BNP level. In addition, the prognostic value of BNP in sepsis remains debatable. In this study, we sought to discover potential independent determinants of BNP elevation in critical sepsis. The prognostic value of BNP was also evaluated.MethodsIn this observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 45 publications
(85 reference statements)
4
64
1
1
Order By: Relevance
“…11,12 Septic patients with poor renal outcomes also had elevated BNP levels at the beginning of their ICU stay (Figure 3). Because volume resuscitation is an important treatment for sepsis, the International Surviving Sepsis Campaign Guidelines Committee recommends fluid management to achieve a target CVP level.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11,12 Septic patients with poor renal outcomes also had elevated BNP levels at the beginning of their ICU stay (Figure 3). Because volume resuscitation is an important treatment for sepsis, the International Surviving Sepsis Campaign Guidelines Committee recommends fluid management to achieve a target CVP level.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, many investigators have reported an association between the absolute BNP level and mortality in critically ill patients. 11,12 Therefore, our hypothesis was that the BNP level could also predict renal outcome and it has the potential to be a convenient cost-effective marker for fluid management in critically ill patients. The first aim of our study was to specify the association between the delta-BNP level and patient outcomes (i.e., AKI occurrence, recovery, and mortality).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with sepsis, a higher BNP level indicates a worse prognosis. 17 BNP levels are similar in patients with septic shock and cardiac emergencies; therefore BNP cannot be used to differentiate cardiac and septic shock. 18 BNP could also help determine the optimum time for weaning from mechanical ventilation: Mekontso-Dessap et al 19 reported that among 102 patients undergoing ventilation weaning, patients who failed the weaning or who had successful ventilation weaning but failed extubation had a significantly higher BNP level than patients with successful ventilation weaning and extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report showed that inflammation increases the plasma BNP level (24). In septic patients, the severity of the illness is the main determinant of the BNP level, rather than cardiac function (25).…”
Section: Plasma Bnp Levels In Non-heart Failure Patientsmentioning
confidence: 98%